Menstrual hygiene practices in young girls of urban India - Wagh, Reena V.; Upadhye, Aditi J.; Upadhye, Jayshree J. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Menstrual hygiene is an important aspect in the life of young girls.The present study aims at assessing the knowledge regarding menstruation and hygienic practices and perceptions during menstruation. Methods: It was a cross sectional study, conducted among 100 young girls of 20-22 years age to assess the awareness of menstrual hygiene. Data was collected by pre-tested questionnaire. Statistics was calculated in percentages. Results: Out of 100 girls, 71 (71%) knew about menstruation before menarche while 29 (29%) did not have any knowledge. 71 (71%) girls knew the cause of menstruation as physiological, 18 (18%) girls didn’t know the cause, 11 (11%) girls still believe it as curse of God. 68 (68%) girls knew the source of bleeding during menstruation as uterus, 20 (20%) girls thought it as vagina while 12 (12%) thought it as urethra. 64% girls use sanitary pads during menstruation, 19% girls used old cloth while 17% girls used new cloth during menstruation as adsorbent material. 9% girls dispose pads or used cloth in dustbin, 19% girls flush them in toilet while 12% girls throw them roadside. 96% girls avoid going to temple, 68% girls restrict their daily activities, 56% girls avoid going to functions, 50% girls avoid going to kitchen, 50% girls avoid going to kitchen while 45% girls avoid touching things at home. Conclusions: It is very important that young girls should be educated about the importance of maintaining hygiene during menstruation to prevent the risk of reproductive tract infections.